2020
DOI: 10.1002/ece3.6190
|View full text |Cite
|
Sign up to set email alerts
|

Friend or foe? A parasitic wasp shifts the cost/benefit ratio in a nursery pollination system impacting plant fitness

Abstract: Nursery pollination systems are species interactions where pollinators also act as fruit/seed herbivores of the plant partner. While the plants depend on associated insects for pollination, the insects depend on the plants' reproductive structures for larval development. The outcome of these interactions is thus placed on a gradient between mutualism and antagonism. Less specialized interactions may fluctuate along this gradient with the ecological context, where natural enemies can play an important role. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 91 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…Plant species from the Caryophyllaceae family (Silene, Stellaria spp.) were the subject of several studies focused mostly on attraction for pollinators [54] or herbivore moths and their parasitoids [55,56]. In this study, the Caryophyllaceae found in vineyard inter-rows were Arenaria serpyllifolia L., Stellaria media L.…”
Section: Insect Occurrence and Diversitymentioning
confidence: 76%
“…Plant species from the Caryophyllaceae family (Silene, Stellaria spp.) were the subject of several studies focused mostly on attraction for pollinators [54] or herbivore moths and their parasitoids [55,56]. In this study, the Caryophyllaceae found in vineyard inter-rows were Arenaria serpyllifolia L., Stellaria media L.…”
Section: Insect Occurrence and Diversitymentioning
confidence: 76%
“…Our greatest reserve is toward figure 5b in the original paper (Villacañas de Castro & Hoffmeister, 2020) and the conclusions derived from it. We recognize that the authors make a good point of making a graph to compare the presence of density‐dependent effects on the probability of germination and survival of plants, but we claim that their choice of what to graph was erroneous for their main purpose.…”
Section: Survival Probability Versus Number Of Survivorsmentioning
confidence: 93%
“…Original dataset from Villacañas de Castro & Hoffmeister (2020) Dryad:doi.org/10.5061/dryad.rjdfn2z75.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 2 more Smart Citations